Nutcracker ballet : the story of the. . - Hautzig, Deborah (New York : Random House, 1983)
Relates the story of the popular ballet, in which a little travels with the Nutcracker Prince to the Land of Sweets.
Keywords: Nutcracker (Ballet) - Juvenile literature; Nutcracker (Ballet); Ballets - Stories, plots, etc